Asleep on the job: Can night shift napping provide greater safety for both staff and patients? - Jennifer Gamble; Paula Foran (Journal of Perioperative Nursing)
Fatigue presents as an all-pervasive challenge to anyone who is engaged in shift work. While this affects all nurses, those who work on night duty have been shown to have the greatest risk of fatigue and cognitive impairment thus potentially posing a higher safety risk to themselves, the patients under their care and the wider community as nurses make their way home driving while drowsy.